PROMPTING STUDENT’S WRITING FOCUS AND CONTENT THROUGH INKSHEDDING: Inkshedding, Blog, Focus, Content, Blended learning - Rahayu, Endah Yulia (Fakultas Pedagogi dan Psikologi Universitas PGRI Adi Buana Surabaya, 2010)
One of the propositions of inkshedding was that it could broaden opportunity of everyone’s expressing their ideas in written form by inviting others to read and comment on the written ideas. These comments were supposed to assist the writers to improve their writing and to make their ideas easily ‘heard’. Therefore, I utilized the idea provocation technique - inkshedding in my research to see the improvement of the focus and content of the written ideas. Focus was the single controlling point made with an awareness of task (mode) about specific topic while content was The presence of ideas developed through facts, examples, anecdotes, details, opinions, statistics, reasons, and/or explanations. I collected the research data from the written comments made by 13 out of the 38 students joining my class who completed all the six inkshedding tasks. Their comments were posted online in the blog and mailing list. To validate my study, I invited my a senior colleague to be the investigator triangulator by examining the written ideas, in term of the quality of focus and content using the same assessment rubric as I did. My and his scores were then correlated using Pearson correlation coefficient and the result was 93.50% for focus and 94.30% for content, which meant there was high positive correlation between my scoring and the investigator’s. This was an indication of the validity of the scoring.